Combining Miconazole and Domiphen Bromide Results in Excess of Reactive Oxygen Species and Killing of Biofilm Cells - Tits, Jana; Berman, Judith; Cammue, Bruno P. A.; Thevissen, Karin (Frontiers in Cell and Developmental Biology, 2021)
Fungal biofilm-related infections are increasingly occurring. We previously identified a fungicidal antibiofilm combination, consisting of miconazole (MCZ) and the quaternary ammonium compound domiphen bromide (DB). DB eliminates tolerance rather than altering the susceptibility to MCZ of various Candida spp. Here we studied the mode of action of the MCZ-DB combination in more detail. We found that DB’s action increases the permeability of the plasma membrane as well as that of the vacuolar membrane of Candida spp.. Furthermore, the addition of DB affects the intracellular azole distribution. MCZ is a fungicidal azole that, apart from its well-known inhibition of ergosterol biosynthesis, also induces accumulation of reactive oxygen species (ROS). Interestingly, the MCZ-DB combination induced significantly more ROS in C. albicans biofilms as compared to single compound treatment. Co-administration of the antioxidant ascorbic acid resulted in abolishment of the ROS generated by MCZ-DB combination as well as its fungicidal action. In conclusion, increased intracellular MCZ availability due to DB’s action results in excess of ROS and enhanced fungal cell killing.